Key Technology on Middleware-based Dynamic Traffic Information Platform - Lei Wu; Tai Yang; Licai Yang (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
According to traffic information of multi-source heterogeneity and complexity of information processing, the architecture of the dynamic traffic information platform based on middleware is proposed, which enhanced the system stability, generality, and efficiency depending on the high integration and scalability of middleware. This middleware-based platform unifies and encodes the data from all sorts of detectors, and integrates the multi-mode transmission, data preprocessing, and data fusion. On the publishing stage, this platform realizes the interactions between different publishing devices and traffic database through an independent traffic information publishing middleware. The proposed platform overcomes the data loss and data noise, decreases the data redundancy due to the heterogeneous multi-source data, and ensures the data accuracy with better security and expandability. The performance is efficient, reliable with cross-platform information transmission.